2021
DOI: 10.1096/fj.202001879rr
|View full text |Cite
|
Sign up to set email alerts
|

CHO/LY‐B cell growth under limiting sphingolipid supply: Correlation between lipid composition and biophysical properties of sphingolipid‐restricted cell membranes

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 85 publications
(183 reference statements)
5
13
0
Order By: Relevance
“…Flow-cytometry analyses demonstrated that 84% of CHO cells grown in SL-deficient medium for 72 h and treated with 2.5 µM myriocin remained viable (Fig. 1 C), similar to the 86% value obtained with non-treated LY-B cells grown in SL-deficient medium 13 . Values for Myr-treated LY-B cells were the same as for the non-treated ones.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…Flow-cytometry analyses demonstrated that 84% of CHO cells grown in SL-deficient medium for 72 h and treated with 2.5 µM myriocin remained viable (Fig. 1 C), similar to the 86% value obtained with non-treated LY-B cells grown in SL-deficient medium 13 . Values for Myr-treated LY-B cells were the same as for the non-treated ones.…”
Section: Resultssupporting
confidence: 79%
“…Results are occasionally shown of cells grown in myriocin-free, SL-deficient medium. The latter are only for comparative purposes, they have been published in 13 . Cell count measurements were performed using a BioRad TC20 hemocytometer to assess myriocin treatment effects on CHO (wild type) and LY-B (SPT-defective) cell division rate and integrity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations